author Jim Pryor Tue, 2 Nov 2010 13:06:40 +0000 (09:06 -0400) committer Jim Pryor Tue, 2 Nov 2010 13:06:40 +0000 (09:06 -0400)
Signed-off-by: Jim Pryor <profjim@jimpryor.net>

index 044d973..a6165e9 100644 (file)
@@ -194,7 +194,7 @@ We also need to designate for `M` a "join" transformation, which is a natural tr

These two natural transformations have to satisfy some constraints ("the monad laws") which are most easily stated if we can introduce a defined notion.

-Let <code>&phi;</code> and <code>&gamma;</code> be members of `T`, that is they are natural transformations from `F` to `MF'` and from `G` to `MG'`, respectively. Let them be such that `F' = G`. Now `(M &gamma;)` will also be a natural transformation, formed by composing the functor `M` with the natural transformation <code>&gamma;</code>. Similarly, `(join G')` will be a natural transformation, formed by composing the natural transformation `join` with the functor `G'`; it will transform the functor `MMG'` to the functor `MG'`. Now take the vertical composition of the three natural transformations `(join G')`, <code>(M &gamma;)</code>, and <code>&phi;</code>, and abbreviate it as follows:
+Let <code>&phi;</code> and <code>&gamma;</code> be members of `T`, that is they are natural transformations from `F` to `MF'` and from `G` to `MG'`, respectively. Let them be such that `F' = G`. Now <code>(M &gamma;)</code> will also be a natural transformation, formed by composing the functor `M` with the natural transformation <code>&gamma;</code>. Similarly, `(join G')` will be a natural transformation, formed by composing the natural transformation `join` with the functor `G'`; it will transform the functor `MMG'` to the functor `MG'`. Now take the vertical composition of the three natural transformations `(join G')`, <code>(M &gamma;)</code>, and <code>&phi;</code>, and abbreviate it as follows:

<pre>
&gamma; <=< &phi;  =def.  ((join G') -v- (M &gamma;) -v- &phi;)
@@ -204,20 +204,20 @@ Since composition is associative I don't specify the order of composition on the

In other words, `<=<` is a binary operator that takes us from two members <code>&phi;</code> and <code>&gamma;</code> of `T` to a composite natural transformation. (In functional programming, at least, this is called the "Kleisli composition operator". Sometimes its written <code>&phi; >=> &gamma;</code> where that's the same as <code>&gamma; <=< &phi;</code>.)

-&phi; is a transformation from `F` to `MF'` which = `MG`; `(M &gamma;)` is a transformation from `MG` to `MMG'`; and `(join G')` is a transformation from `MMG'` to `MG'`. So the composite &gamma; <=< &phi; will be a transformation from `F` to `MG'`, and so also eligible to be a member of `T`.
+<code>&phi;</code> is a transformation from `F` to `MF'` which = `MG`; <code>(M &gamma;)</code> is a transformation from `MG` to `MMG'`; and `(join G')` is a transformation from `MMG'` to `MG'`. So the composite <code>&gamma; <=< &phi;</code> will be a transformation from `F` to `MG'`, and so also eligible to be a member of `T`.

Now we can specify the "monad laws" governing a monad as follows:

(T, <=<, unit) constitute a monoid

-That's it. (Well, perhaps we're cheating a bit, because &gamma; <=< &phi; isn't fully defined on `T`, but only when `F` is a functor to `MF'` and `G` is a functor from `F'`. But wherever `<=<` is defined, the monoid laws are satisfied:
+That's it. Well, there may be a wrinkle here. I don't know whether the definition of a monoid requires the operation to be defined for every pair in its set. In the present case, <code>&gamma; <=< &phi;</code> isn't fully defined on `T`, but only when `F` is a functor to `MF'` and `G` is a functor from `F'`. But wherever `<=<` is defined, the monoid laws are satisfied:

-       (i) &gamma; <=< &phi; is also in T
-       (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
+           (i) &gamma; <=< &phi; is also in T
+          (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
(iii.1) unit <=< &phi;  =  &phi;                 (here &phi; has to be a natural transformation to M(1C))
(iii.2)                &phi;  =  &phi; <=< unit  (here &phi; has to be a natural transformation from 1C)

-If &phi; is a natural transformation from `F` to `M(1C)` and &gamma; is `(&phi; G')`, that is, a natural transformation from `PG` to `MG`, then we can extend (iii.1) as follows:
+If <code>&phi;</code> is a natural transformation from `F` to `M(1C)` and <code>&gamma;</code> is <code>(&phi; G')</code>, that is, a natural transformation from `FG` to `MG`, then we can extend (iii.1) as follows:

&gamma; = (&phi; G')
= ((unit <=< &phi;) G')
@@ -227,7 +227,7 @@ If &phi; is a natural transformation from `F` to `M(1C)` and &gamma; is `(&phi;
??
= (unit G') <=< &gamma;

-where as we said &gamma; is a natural transformation from some `PG'` to `MG'`.
+where as we said <code>&gamma;</code> is a natural transformation from some `FG'` to `MG'`.

Similarly, if &phi; is a natural transformation from `1C` to `MF'`, and &gamma; is `(&phi; G)`, that is, a natural transformation from `G` to `MF'G`, then we can extend (iii.2) as follows: